The impact of Accounting Information System on Internal Audit Effectiveness: the moderation of Audit Committee in Oman - Alsabti, Haider Alaaldin Abdul Wahab (2022)
The aim of this research is to investigate the impact of Accounting Information System (AIS) on Internal Audit Effectiveness (IAE) among companies listed in Muscat Securities Market (MSM) by focusing on the moderating impact of Audit Committee (AC). One of the problems facing companies listed on the MSM in Oman is the absence of an understanding of how accounting information system factors can encourage internal auditors through the support of the audit committee to achieve effectiveness. The theoretical foundation for this research was built based on the stewardship theory. A quantitative approach was used to collect data from a group of respondents consisting of financial/account manager, accountant, internal auditor, and audit committee member, who were selected through an expert sampling technique. SPSS and Smart- PLS were used to analyze the data. The questionnaire was administered three times. The first administration involved a pilot test to investigate the reliability of the questionnaire involving 60 respondents. For the second administration, the questionnaire was distributed to 100 respondents to conduct an exploratory factor analysis to verify that the research variables could actually measure their impacts. For the third administration, the questionnaire was distributed to 397 respondents to conduct a confirmatory factorial analysis. The results of the study found that, the first direct hypothesis that examined the impact of reliability on internal audit effectiveness in companies listed in MSM showed a positive and significant impact, at = 0.255, tvalue = 3.985 and p-value = 0.000. The second direct hypothesis which examined the impact of relevance on internal audit effectiveness revealed a positive and significant impact, at = 0.200, t-value = 2.835 and p-value = 0.005. The third direct hypothesis which examined the impact of integration on internal audit effectiveness revealed a positive and significant impact, at = 0.107, t-value = 2.002 and p-value = 0.046. The fourth direct hypothesis which examined the impact of flexibility on internal audit effectiveness revealed a positive and significant impact, at = 0.197, t-value = 3.568 and p-value = 0.000. Moreover, audit committee moderated the impact of accounting information system on internal audit effectiveness. In implication, companies should focus on audit committee to increase the knowledge of the accounting information system factors reliability, relevance, integration and flexibility.